Sources of autonomy support, subjective vitality and physical activity behaviour associated with participation in a lunchtime walking intervention for physically inactive adults - Kinnafick, F.; Thøgersen-Ntoumani, Cecilie; Duda, J.; Taylor, I. (Elsevier BV, 2014)
Based on Basic Needs Theory (BNT: Deci & Ryan, 1985), this study examined longitudinal relationships between autonomy support from two sources, psychological need satisfaction, subjective vitality and self-reported physical activity during a walking intervention for physically inactive adults. We proposed that autonomy support provided via a walk leader and the overall programme would independently predict change in subjective vitality and physical activity from baseline to week 16 (post-intervention) and at four month follow-up. Further, we proposed that direct relationships among sources of autonomy support and outcomes would be mediated by autonomy, relatedness, and competence need satisfaction.